Structural health monitoring and damage detection for composite panel structures via statistical analysis - Ali Al-Adnani, Nisreen N. (2015)
Rectangular panels with or/and without mass loading are widely applied in civil,aerospace and mechanical engineering. Changes such as cracks, corrosion or drilled holes can affect the structure and integrity of components. This study focuses on three (3) parts of experimental works: firstly, to fabricate the three types of composite materials panels; secondly, to assess the mechanical properties, the micro structure and thermal analysis of the materials, and thirdly, to detect the damage by using smart sensor to appraise the Structural Health Monitoring (SHM) technique and damage identification. To do this, aluminium alloy type 6061-T6 and three fabricated composite materials are utilized. These composites are combined with epoxy resin as a matrix mixed individually with Twill Weave 240 g/m² carbon fiber (CFW), Plain Weave 300 g/m² Glass Fiber (GFW) and Chopped Strand Mats 450 g/m² glass fiber [GF (CSM)] as fillers. This study also includes the fabrication procedure of the three types of composite panels by using hand lay-up and vacuum bagging process. Al 6061-T6 is considered as a reference material in order to evaluate the characterizations of the new composite materials. Moreover, each material has a case study and eventually this research has four case studies. The first case (undamaged) is considered as a reference or the baseline standard data. Crack’s damages are simulated variedly in the panels to reflect the three damage cases in length such as 10 mm, 15 mm and 20 mm. Piezoelectric ceramic Lead Zirconate Titanate (PZT) transducer as a sensor is used to acquire the real time data. The comparison is carried out for damage detection and identification, based on the natural frequency approach and power spectrum with accuracy performance via signal from smart sensor (PZT). Root Mean Square Deviation (RMSD) index and Frequency Reduction Index (FRI) as statistical analysis methods for damage magnitude are performed to improve the SHM technique. RMSD out coming improves the damages identification, when the crack is increased RMSD is increased as well. Finally, SHM approach using PZT is improved and eventually very noticeable and probable changes in the natural frequency are observed, particularly when the damaged depth is increased in the composites. Meanwhile, the comparison between the CFW reinforced epoxy resin and the two glass fiber reinforced epoxy include the micro structure, thermoplastic analysis and mechanical properties. In general, CFW as a composite improved a higher micro structure, thermal analysis and mechanical properties and higher resistance against the vibration effect which is more than the two types of investigated glass fibers.